Sujeito e alteridade em Paul Ricoeur e Emmanuel Lévinas: proximidades e distâncias - Douek, Sybil Safdie (2009)
The present dissertation intends to confront Paul Ricoeur and Emmanuel Levinas philosophy, from an essential point of view: the relationship between the subject and the other, subjectivity and alterity. Question which relevance seems to be dramatic after the Two World Wars, particularly after the Shoah: which could be, subsequent to this historical experience, the meanings of words such as subject, man and ethics? Aware of the necessary and indispensable critics toward classic humanism, and willing to withdraw the subject of his central position in philosophy, since Descartes, both authors seem to rehabilitate the subject, and put again faith in him, without paying to the subject unrestricted reverence. The result is the idea of a subject that includes in itself alterity: self as another , says Ricoeur; the other in the same , says Levinas. But which is the place assigned to the other? Levinas insists in the absolute priority of the other, and proposes the deposition of the subject in behalf of the other: the subject substitutes himself to the other, it is hostage of the other, being absolutely passive in his relationship with him. Ricoeur, in his turn, defends the importance of both (oneself and other) and prefers to think in terms of reciprocity, and receptivity of the subject. These different perspectives concerning relationship between subject and other imply two conceptions of ethics: for Levinas, ethics of responsibility and election; for Ricoeur, ethics of promise, of good living together and mutuality. It implicates also two different attitudes in regard of a question not always considered as philosophical: transcendence or the Name of God. For both, God is a question which deserves attention, but Ricoeur excludes the Name of his philosophical speech, building a hermeutics of the self without the support of transcendence; while for Levinas, the problem of subjectivity goes along this the problem of transcendence. Therefore, a question is born: the presence or absence of the Name of God in their philosophy of subjectivity could have connections or correspondences with their respective religious traditions Ricoeur´s Protestantism and Levinas Judaism? Traditions never denied by both of them, although kept far from their philosophical reflections, each one in his own way